Long-term perceived disabilities up to 10 years after transient ischaemic attack - Jenni Andersson; Britt-Marie Stålnacke; Ann Sörlin; Gustaf Magaard; Xiaolei Hu (Medical Journals Sweden, 2021)
Background: The long-term impact of transient ischaemic attack is largely unknown. Objectives: To assess the long-term perceived impact of transient ischaemic attack and explore the influence of sex and age on these perceptions; and to evaluate the relationships between activities of daily living, participation and overall recovery, and the other domains of the Stroke Impact Scale 3.0 (SIS). Methods: A retrospective study among adult community-dwelling individuals from 6 months up to 10 years after onset of transient ischaemic attack. A total of 299 survivors of transient ischaemic attack responded to the SIS. Results: Most self-reported disabilities involved emotion, strength, and participation domains of SIS and remained stable until 10 years post-transient ischaemic attack. Women reported significantly more disabilities for emotion and hand function. Elderly subjects (age > 65 years) reported more disabilities for strength, mobility, hand function, activities of daily living/instrumental activities of daily living, and participation. The activities of daily living/instrumental activities of daily living, participation, and overall recovery demonstrated significant, although low-to-moderate, associations with other SIS domains after transient ischaemic attack. Conclusion: The broadly perceived disabilities were demonstrated consistently and played a significant meaningful role in everyday life and recovery among community-dwelling individuals up to 10 years after a transient ischaemic attack. These findings indicate the need for long-term multi-professional follow-up with holistic rehabilitation to improve overall recovery among survivors of transient ischaemic attack.